The use of digital technologies in spatial geometry teaching: a literature review (Research, Society and Development, 2021)
Learning mathematics has always caused discomfort for many students, especially during high school, a period of deepening in some areas, such as the study of spatial geometry, a complex subject to be addressed in the classroom. Objective: The purpose of this study was to search the literature to find evidences about the use of new digital technologies in teaching and learning spatial geometry. Methodology: for the research, the search terms, the databases, and the inclusion and exclusion criteria were defined. Results: After searching the main national and international databases, ten articles were selected for reading, and two of them partially meet the proposed objectives. The first one proposes a computational system for three-dimensional modeling from planes and lines, however, it uses outdated technologies, while the second one studies learning, but only of beginning mathematics teachers, and not of students. Considering the same previous methodological criteria, a second search was carried out with the inclusion of the expression "augmented reality", resulting in five articles, which are also briefly described in Results. Conclusion: the results obtained allow us to conclude that, although the literature shows relevant works associating the teaching and learning of Spatial Geometry with digital technologies, most of them describe only the study of geometric solids, where other themes of this area are not considered, such as relative positions between points, lines and planes in space.